Impact-resistant polypropylene/Natural rubber blends - Mathew N M; Tinker A J (Journal of Natural Rubber Research, 1986)
It has been demonstrated previously that blends of polypropylene with natural rubber having high impact strength at low temperatures may be prepared by blending in the presence of m-phenylenebismaleimide. The potential for a cheaper additive system, phenolformaldehyde resin with zinc oxide, to replace the m-phenylenebismaleimide has been investigated. The resin and zinc oxide at least as effective as m-phenylenebismaleimide in increasing both the notched Izod and falling weight impact strength of the blends at low temperatures. Other properties are also generally affected in a similar manner. The effect of the level of resin and zinc oxide on impact strength is considered in terms of the mechanisms leading to increased impact strength and appropriate levels of resin and zinc oxide are identified. There is a considerable cost advantage in the use of resin and zinc oxide.
Keywords: Natural rubber blends